(untitled) (Journal of Global Arts Studies, 2024)
Background: China’s digital cultural industry has developed rapidly in recent years. Domestic scholars have also conducted a lot of research on it from the definition, development format, and theoretical level. However, it is urgent to clarify its research trends and hot spots to guide future research directions. Objective: This study analyzes the hot trend of research on China’s digital cultural industry to grasp the direction of digital cultural industry development. Methods: Based on literature research, the author systematically combs and reviews previous related research and explores the current development status and future development trends of China’s digital cultural industry through a speculative method. Results: Through a systematic literature review, it can be found that in the previous research of domestic scholars on China’s digital culture, a single analysis of the industry is conducted, which provides a deep research foundation for the definition of the concepts of cultural industry, digital cultural industry, and digital content consumption. However, there are still deficiencies in research methods and research content. Conclusion: In subsequent research, innovative research methods can focus on integrating the digital cultural industry and technology and the hot trends of the digital cultural content consumption market.